PROVERBS AND MODERNITY: TAKING THE PROVERBS OUT OF THE MOUTH OF THE ELDERS - Daniel, Iyabode Omolara Akewo (Proverbium - Yearbook, 2016)
Proverbs have usually been considered the preserve of the elders in the society because they are seen as the repository of the wisdom of the race. However, the creativity that comes with the youthful incursion into proverbial expression is not considered a serious communicative occurrence in Nigeria. This paper thus investigates the use of proverbs as a sign of communicative creativity by the youth as well as linguistic dynamism. Ethnographic and linguistic instruments were employed in investigating different proverbs from a Nigerian language, Yoruba. The original proverbs and their post-proverbial forms were presented and the essence of modern adaptation as a feature of linguis-tic dynamism as well as communicative creativity were presented. It is argued that this linguistic posturing exposes the communicative dyna-mism that exists in Nigerian languages to fit into the postmodern con-text and relevance of proverbs in the twenty-first century world of the Nigerian society.